EUROCOVER-CLL: Reimbursement and accessibility of new treatments in relapsed/refractory chronic lymphocytic leukemia - Monica, Magdalena; Becirovic, Sabina; Bianchi-Manaila, Ioana; Duborija-Kovacevic, Natasa; Draganic, Pero; Garouliene, Kristina; Hammerman, Ariel; Ispan, Fanni; Ivanova, Boryana; Männik, Agnes; Meresz, Gergo; Nazaryan, Lusine; et al. (Frontiers in Pharmacology, 2025)
BackgroundDespite recent therapeutic advances in chronic lymphocytic leukemia (CLL), access to innovative treatments may still be uneven outside Western Europe. This study aimed to explore reimbursement policy and access to novel targeted CLL therapies across selected countries and to analyze factors associated with differences in treatment availability and reimbursement timelines.MethodsReimbursement frameworks, timelines, and accessibility of six novel CLL therapies were assessed across 15 countries in Central and Eastern Europe, the Balkans, Armenia, and Israel. Data were collected via expert surveys in late 2024, based on publicly available national and regional sources. The survey covered reimbursement extent, timelines, policy restrictions, coverage pathways, and health technology assessment (HTA) evaluations. Comparative analyses examined regional differences in reimbursement and their potential drivers. Spearman’s rank correlation was used to explore associations between the number of reimbursed therapies, reimbursement delays, and demographic, macroeconomic, and epidemiological variables.ResultsThe number of reimbursed therapies ranged from zero (Ukraine, Armenia) to five (Czech Republic), with a regional mean of 2.7 (SD = 1.38) and overall mean time to reimbursement of 29.3 months (SD = 21.4). Ibrutinib, reimbursed in 13 countries, had the longest mean reimbursement delay (35.6 months), while venetoclax (11 countries, 26.5 months), acalabrutinib (9 countries, 16.4 months), and zanubrutinib (6 countries, 15.2 months) had shorter delays. Gross domestic product (GPD) per capita showed a moderate positive correlation with the number of reimbursed therapies (ρ = 0.673, p = 0.006). Borderline significant associations were noted for CLL incidence and mortality (p = 0.050). Reimbursement indications were often restricted, particularly for patients without deletion 17p or TP53 mutations who experienced late relapses. Data on HTA outcomes and the number of treated patients were limited in several countries, and common challenges included funding constraints, administrative barriers, and the lack of centralized rare disease policies.ConclusionSignificant disparities in access to targeted CLL therapies persist across the analyzed countries, with the number of reimbursed therapies positively correlated with GDP per capita.